Trade facilitation and global warming: based on cross-country panel data - Ying Jiang (Frontiers in Environmental Science)
This study delves into the intricate interplay between trade facilitation and global warming, emphasising the ramifications of trade facilitation on climate change dynamics. To quantify the effects of trade facilitation on global warming, this research employed both spatial econometric and traditional econometric models, leveraging data spanning 129 countries from 2010 to 2019. The empirical findings reveal a notable direct negative correlation between trade facilitation and global warming. This negative impact arises from optimised resource allocation, the acceleration of green technology development, and the facilitation of industrial green transformation. Intriguingly, the study also indicates an absence of significant spillover effects from trade facilitation on neighbouring regions. Moreover, the relationship between trade facilitation and global warming is linear, devoid of any non-linear associations. A deeper mechanism analysis elucidates that trade facilitation primarily mitigates global warming by reducing carbon emissions and fostering technological innovation, particularly in developed economies. In stark contrast, this impact is less pronounced in developing countries, primarily due to constraints in technology and policy frameworks. This nuanced understanding underscores the importance of context-specific considerations when assessing the environmental implications of trade facilitation. The study culminates in a series of policy prescriptions aimed at bolstering green trade facilitation measures, fostering innovation, enhancing regional cooperation, and formulating policies tailored to the needs of developing countries. These recommendations strive to strike a delicate balance between mitigating global warming and promoting economic growth, thereby illustrating the potential for trade facilitation to serve as a dual catalyst for environmental sustainability and economic prosperity.